Spontaneous bladder dome rupture, a rare association with extraperitoneal leakage - Mustfar, Siti Nor Suzeana; Halim Lim, Aidi Aswadi (2021)
SPONTANEOUS BLADDER DOME RUPTURE, A RARE ASSOCIATION WITH EXTRAPERITONEAL LEAKAGE. Siti Nor Suzeana Mustfar*1 ; Aidi Aswadi Halim Lim1 1Department of Radiology, International Islamic University Malaysia